2015
DOI: 10.1186/s12893-015-0067-4
|View full text |Cite
|
Sign up to set email alerts
|

Partial axillary lymph node dissection inferior to the intercostobrachial nerves complements sentinel node biopsy in patients with clinically node-negative breast cancer

Abstract: BackgroundThe practice of breast cancer diagnosis and treatment in China varies to that in western developed countries. With the unavailability of radioactive tracer technique for sentinel lymph nodes biopsy (SLNB), using blue dye alone has been the only option in China. Also, the diagnosis of breast malignant tumor in most Chinese centres heavily relies on intraoperative instant frozen histology which is normally followed by sentinel lymph nodes mapping, SLNB and the potential breast and axillary operations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…However, the practice of axillary evaluation used in our center, including preoperative US assessment of axillary nodes, a higher proportion of US-guided FNAC on axilla (60.4%), and frozen section analysis of sentinel lymph nodes, may have partly reduced the sentinel lymph node identification failure and false-negative rates. 28 In addition, Li et al 29 reported that 97.8% of patients (44 of 45) with false-negative sentinel lymph node biopsy results by using methylene blue dye alone were found to have only 1 or 2 metastatic nodes on final pathology analysis. Therefore, the sentinel lymph node mapping technique used in this study might had have little effect on the extent of axillary nodal involvement, which was categorized into limited positive nodes (without or with <3 metastatic lymph nodes) and several positive lymph nodes (≥3 metastatic nodes) for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the practice of axillary evaluation used in our center, including preoperative US assessment of axillary nodes, a higher proportion of US-guided FNAC on axilla (60.4%), and frozen section analysis of sentinel lymph nodes, may have partly reduced the sentinel lymph node identification failure and false-negative rates. 28 In addition, Li et al 29 reported that 97.8% of patients (44 of 45) with false-negative sentinel lymph node biopsy results by using methylene blue dye alone were found to have only 1 or 2 metastatic nodes on final pathology analysis. Therefore, the sentinel lymph node mapping technique used in this study might had have little effect on the extent of axillary nodal involvement, which was categorized into limited positive nodes (without or with <3 metastatic lymph nodes) and several positive lymph nodes (≥3 metastatic nodes) for analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In the present study, the FNR was 5.48% in patients who underwent ALND. Other researchers have reported that peripheral lymph node sampling 13 or atrial ALND 14 may further reduce the FNR of SLNB. However, more extensive surgery may lead to more unnecessary injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, ALND is associated with lymphedema, arm pain, sensory defects, decreased range of motion, and other morbidities that could impair quality of life. Sentinel lymph node biopsy can decrease the risk of these morbidities and has become a standard method for the evaluation of axillary lymph nodes [19][20][21][22]27]. However, ALND remains standard care for patients with a clinically positive lymph node before neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[18,23,28,29]. Since then, many surgeons have considered less invasive techniques than ALND, including AS, sentinel lymph node dissection, or partial ALND [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation